Minnesota history. - Heilbron, Bertha L.; Blegen, Theodore Christian; Buck, Solon J.; Minnesota Historical Society. (Minnesota Historical Society., 1915)
Vols. 2-6 include the 19th-23d Biennial reports of the Society, 1915/16-1923/24 (in v. 2-3 as supplements, in v. 4-6 as extra numbers).
Editors: Feb. 1915-Nov. 1922, S.J. Buck. Feb. 1923-<Dec. 1939> T.C. Blegen (with Bertha L. Heilbron, Mar. 1929-<Dec. 1939>
Vol. 4, no. 5/6 (Feb./May 1922) was issued in 1923, and v. 4, no. 7/8 (Aug./Nov. 1922) in Oct. 1924
Vols. 2-6 include the 19th-23d Biennial reports of the Society, 1915/16-1923/24 (in v. 2-3 as supplements, in v. 4-6 as extra numbers).
Vols. 1-10, 1915-29. 1 v.
Keywords: Minnesota. / fast / (OCoLC)fst01204560; Minnesota / History / Periodicals.; Periodicals. / fast / (OCoLC)fst01411641; History. / fast / (OCoLC)fst01411628